2004
DOI: 10.1007/s00345-004-0411-2
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative imaging in renal cell cancer

Abstract: Renal cell cancer (RCC) represents the fifth most common cancer in men, with a rising incidence. Radical cancer surgery remains the only curative treatment in localized and advanced RCC. Therefore, preoperative imaging is most important for the planning of the surgical approach and strategy. The aim of any preoperative imaging in RCC is to differentiate benign from malignant lesions, to adequately assess tumor size, localization and organ confinement, to identify lymph node and/or visceral metastases, and to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
56
0
8

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(66 citation statements)
references
References 46 publications
2
56
0
8
Order By: Relevance
“…In preoperative staging of the RCC, every patient should have chest X-rays and if lung metastasis is suspected chest CT should be performed (16). If bone metastases are suspected bone scintigraphy should be performed as well as cerebral CT or MRI if brain metastases are suspected (16). In this study, MRI revealed a small liver metastasis in one patient who was staged M1.…”
Section: Spero Brkljacicmentioning
confidence: 65%
See 1 more Smart Citation
“…In preoperative staging of the RCC, every patient should have chest X-rays and if lung metastasis is suspected chest CT should be performed (16). If bone metastases are suspected bone scintigraphy should be performed as well as cerebral CT or MRI if brain metastases are suspected (16). In this study, MRI revealed a small liver metastasis in one patient who was staged M1.…”
Section: Spero Brkljacicmentioning
confidence: 65%
“…During MRI examination, search for distant metastases is limited to the abdomen and visualized portions of the lung bases and axial skeleton. In preoperative staging of the RCC, every patient should have chest X-rays and if lung metastasis is suspected chest CT should be performed (16). If bone metastases are suspected bone scintigraphy should be performed as well as cerebral CT or MRI if brain metastases are suspected (16).…”
Section: Spero Brkljacicmentioning
confidence: 99%
“…The mortality rate continues to increase, suggesting that the elevation of incidence is not merely driven by better detection of early tumors 12 . Although international studies indicate that up to 60% of renal carcinomas are coincidentally diagnosed by imaging tests still in the asymptomatic phase 13,14 , our sample of patients from a Brazilian…”
Section: Discussionmentioning
confidence: 99%
“…However, MRI is the preferred imaging modality as it reliably defines both the extent of a tumour thrombus and also distinguishes between tumour and bland thrombus. 5 Other less frequently used preoperative imaging modalities include venacavography, Doppler ultrasonograpy and TEE.…”
Section: Discussionmentioning
confidence: 99%